Copeptin: clinical use of a new biomarker - Morgenthaler, Nils G.; Struck, Joachim; Jochberger, Stefan; Dünser, Martin W. (Trends in endocrinology and metabolism, 2008)
Arginine vasopressin (AVP) is a key hormone in the human body. Despite the clinical relevance of AVP in maintaining fluid balance and vascular tone, measurement of mature AVP is difficult and subject to preanalytical errors. Recently, copeptin, a 39-amino acid glycopeptide that comprises the C-terminal part of the AVP precursor (CT-proAVP), was found to be a stable and sensitive surrogate marker for AVP release, analogous to C-peptide for insulin. Copeptin measurement has been shown to be useful in various clinical indications, including the diagnosis of diabetes insipidus and the monitoring of sepsis and cardiovascular diseases. Here we review recent findings regarding the relationship between AVP and copeptin, and affirm the value of AVP as a surrogate marker for AVP.